Media usage, religiosity and gender as determinant of performance in chemistry subject (2016)
This research was designed to investigate the effect of media usage, religiosity and gender on performance in chemistry subject. This study employed survey research design. Two hundred participants (66 males and 134 females) drawn from public Senior Secondary Schools in Ibadan North Local Government Area, Oyo State constituted the study’s sample. The instruments used to collect data included four structured questionnaires - Academic Performance Questionnaire in Chemistry (APQC) (α = .914), Media Questionnaire (MQ) (α = .792), Religiosity Questionnaire (RQ) (α = .735), and Gender Questionnaire (GQ) (α = .899). Chemistry Achievement Test (CHAT) was used to determine performance level and ability difference between male and female. Four research questions were answered and three hypotheses were tested at 0.05 Alpha level of significance. Data were analyzed using Pearson’s Product Moment Correlation and Multiple Regression Analyses. The findings of this study showed that media (r=0.119, df = 199, P< 0.05) is a significant correlate of academic performance in chemistry while religiosity (r= 0.057, df = 199, P> 0.05) and gender (r=0.032, df = 199, P> 0.05) are not. It was also revealed that the three independent variables (media, religiosity and gender) are not joint predictors of academic performance in chemistry (R = 0.125, R square = 0.016, p<0.05). It was evident from the findings that media (beta=.112, 11.2%, t=1.552, p<0.05) had the highest significant contribution to academic performance in chemistry. The results also showed that there is no statistical difference in the ability of male (x=3.89, SD=1.609) and female (x=4.01, SD=1.573) even though 59.5% of the students scored less than 50 in Chemistry Achievement test. The study, therefore, concluded that media is a potent correlate and significant determinant of performance in public Senior Secondary Schools in Ibadan North Local Government Area, Oyo State, Nigeria while religiosity and gender are not.